2019
DOI: 10.1111/ics.12513
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometry‐based proteomics reveals the distinct nature of the skin proteomes of photoaged compared to intrinsically aged skin

Abstract: Objective With increasing age, skin is subject to alterations in its organization, which impact on its function as well as having clinical consequences. Proteomics is a useful tool for non‐targeted, semi‐quantitative simultaneous investigation of high numbers of proteins. In the current study, we utilize proteomics to characterize and contrast age‐associated differences in photoexposed and photoprotected skin, with a focus on the epidermis, dermal–epidermal junction and papillary dermis. Methods Skin biopsies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 75 publications
(79 reference statements)
0
6
0
Order By: Relevance
“…It was demonstrated that the level of collagen is reduced at a rate of 1% annually in different tissue types 9 . Additional to intrinsic factors, extrinsic factors such as the skin photo‐aging phenomenon can also accelerate the aging process by modulating the matrix proteomic combination 69 . In recent years, it has been shown that aging matrix has a tight correlation with cancer 70 .…”
Section: The Matrix In Alterationsmentioning
confidence: 99%
“…It was demonstrated that the level of collagen is reduced at a rate of 1% annually in different tissue types 9 . Additional to intrinsic factors, extrinsic factors such as the skin photo‐aging phenomenon can also accelerate the aging process by modulating the matrix proteomic combination 69 . In recent years, it has been shown that aging matrix has a tight correlation with cancer 70 .…”
Section: The Matrix In Alterationsmentioning
confidence: 99%
“…Protein entities pertinent to these pathways were subsequently used to build pathway-or protein class-specific, experimentally identified interaction networks. MatrixDB (Launay et al, 2015) was used to derive ECM proteins interactions and IntAct (Orchard et al, 2014) for all others. These were then downloaded and visualised using Cytoscape 3.4.0.…”
Section: Pathway Enrichment and Network Analysismentioning
confidence: 99%
“…Label-free proteomic liquid chromatography-tandem mass spectrometry (LC-MS/MS) is a powerful analytical technique used traditionally for the identification and relative quantification of proteins within complex tissue extracts. The technique has enabled the identification of disease and ageing biomarkers based on their relative abundance (Newton et al, 2019); however, the detection of abundance-independent, modification-associated biomarkers in complex protein mixtures remains challenging.…”
mentioning
confidence: 99%
“…As mentioned, its complexity results in difficulties in separating and homogenizing the tissue for mass spectrometric analyses, and the dominance of structural proteins further complicates the process. Consequently, until recently, prior studies have only identified a relatively small fraction of the expressed skin proteome [21,22,33,[35][36][37][38][39]. For example, Mikesh et al [33] analyzed the composition in three skin layers from two anatomical regions, resulting in characterization of about 200 proteins and providing insight into varying protein composition depending on skin layer and skin region.…”
Section: Proteomic Analysis Of Healthy Human Skinmentioning
confidence: 99%